2022
DOI: 10.3390/diagnostics12051111
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Ultrasound Imaging Can Quantify Alterations in Microbubble Velocities in the Renal Vasculature of Rats

Abstract: Super-resolution ultrasound imaging, based on the localization and tracking of single intravascular microbubbles, makes it possible to map vessels below 100 µm. Microbubble velocities can be estimated as a surrogate for blood velocity, but their clinical potential is unclear. We investigated if a decrease in microbubble velocity in the arterial and venous beds of the renal cortex, outer medulla, and inner medulla was detectable after intravenous administration of the α1-adrenoceptor antagonist prazosin. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…This emerging technology provides a substantial advancement in hemodynamic quantification and evaluation of the microcirculation, demonstrating a 10fold improvement in spatial resolution using low imaging frequencies and without compromising the imaging depth of conventional CEUS [79,81,83,84]. Super-resolution ultrasound imaging is capable of mapping vessels less than 100 µm in size [85]. In an in vivo mouse model, Chen et al identified renal micro vessels with a spatial resolution of up to 32 μm using a frame rate of 15.6 MHz [86].…”
Section: Super Resolution Ultrasound Imagingmentioning
confidence: 99%
“…This emerging technology provides a substantial advancement in hemodynamic quantification and evaluation of the microcirculation, demonstrating a 10fold improvement in spatial resolution using low imaging frequencies and without compromising the imaging depth of conventional CEUS [79,81,83,84]. Super-resolution ultrasound imaging is capable of mapping vessels less than 100 µm in size [85]. In an in vivo mouse model, Chen et al identified renal micro vessels with a spatial resolution of up to 32 μm using a frame rate of 15.6 MHz [86].…”
Section: Super Resolution Ultrasound Imagingmentioning
confidence: 99%
“…Recently, SRUS showed a superiority to ultrasound in the evaluation of human kidney allograft vascularization [19]. Additionally, SRUS has been used on rodent kidneys to detect decreased vascular density after acute kidney injury and flow-velocity changes [20][21][22][23]. However, altered renal vascular morphology as a consequence of DKD development has not previously been investigated using SRUS.…”
Section: Introductionmentioning
confidence: 99%
“…For example, unlike sham-operated mice, mice with unilateral ischemia-reperfusion-induced chronic kidney disease had decreased vascular density and increased tortuosity in the renal cortex [19]. In another study, a vasodilator-induced decrease in microbubble velocity was found in the cortex and the deeper-lying medulla of rat kidneys [20], and lastly, increased microbubble velocity was found in the cortical radial arteries of hypertensive rats [21]. The cortical vessels of a human kidney have also been visualized with SRUS [22].…”
mentioning
confidence: 97%
“…So wiesen Mäuse mit einseitiger, durch Ischämie-Reperfusion induzierter, chronischer Nierenerkrankung im Gegensatz zu scheinoperierten Mäusen eine verringerte Gefäßdichte und erhöhte Tortuosität in der Nierenrinde auf [19]. In einer anderen Studie wurde eine durch Vasodilatatoren induzierte Abnahme der Geschwindigkeit von Mikrobläschen im Cortex und im tiefer liegenden Mark von Rattennieren festgestellt [20]. Schließlich wurde eine erhöhte Geschwindigkeit von Mikrobläschen in der kortikalen A. radialis hypertensiver Ratten gefunden [21].…”
unclassified